STABILITY OF PULSATIONAL AMPLITUDE FOR CEPHEIDS OF PERIOD = 6±1d - Abdel-Sabour, M. A. (Одеські астрономічні публікації, 2017)
Fourier decomposition of light curves used to obtain rigorous estimates of the pulsational amplitudes. A limit sample of Cepheids of period = 6±1d,was chosen to demonstrate the capabilities of this technique. The pulsational amplitude shows significant increase and decrease for some stars.